Peran Kelembagaan Perdesaan untuk Keberlanjutan Penerapan SRI di Kabupaten Karawang - Suciati, Luh Putu; Juanda, Bambang; Fauzi, Akhmad; Rustiadi, Ernan (UI Scholars Hub, 2014)
Sustainability of System of Rice Intensification (SRI) requires rural institution role. The study was conducted in Karawang and uses institutional economics approach and logit regression. The analysis shows potential problems of SRI related with principal-agent/institutional relation and economics transaction costs. Strengthening the activities within farmer groups will reduce economics transaction costs in beginning of application. Farmer will choose